Optimization of a cupuaçu (Theobroma grandiflorum) nectar formulation - Vieira, M. M. C. (2013)
A Cupuaçu (Theobroma grandiflorum) nectar formulation was optimized, for European consumers, using an augmented simplex centroid mixture design. the working ranges, x1 (Sugar, 10–25%), x2 (Cupuaçu, 15–30%) and x3 (Water, 60–75%), were based on a common Brazilian recipe. As responses, a sensory panel evaluated taste, acidity, sweetness, viscosity, mouthfeel and overall opinion. For each response, the best mathematical predictive model was chosen, based on Response Surface statistical analysis. an optimization was then performed, and the optimum was Cupuaçu (18.5%), Sugar (11%) and Water (70.5%). Tolerance tests were carried out and, although differences were detected (= 5%), the level of acceptance remained above average.